Computer Architecture in Education. (Communications of the ACM, 2008)
The article discusses the need in higher education for students trained in computer science to be competent in engineering software for parallel systems. Students who graduate with that school, the article states, will be leaders in the industry. Topics include computer architecture classes and universities that need to revise their curricula, students who think about engineering sequential solutions, and parallel programming classes that have been relegated to electives. Also discussed is programming for single-core devices.